[PP.16.23] REVISED DEFINITION OF PREDICTED LEFT VENTRICULAR MASS USING AMBULATORY BLOOD PRESSURE IN HEALTHY KOREAN ADULTS. (September 2016) - Kim, B.; Lee, Y.; Shin, J.; Shin, J.; Lim, Y.; Shim, S.
Abstract : Objective: The left ventricular is known to be influenced by both hemodynamic and non-hemodynamic factors. Body size and gender are the most representative non-hemodynamic factors. This study was performed to establish the influences of these variables including ambulatory BP on the variation of the left ventricular mass in healthy Korean adults. Design and method: 627 subjects (male = 270, female = 357), with a normal body mass index and blood pressure, were included in the analysis form database of the Yangpyung Epidemiologic cohort. The left ventricular mass was calculated using the equation: [1.04 × (IVSd + LVDd + PWTd)3-(LDVs3)] × 0.8 + 0.6. The stroke volume was calculated (mL/beat) using Teichholz's formula. The stroke work (SW in gram-meters/beat [g-m/beat]) was computed as ambulatory systolic BP × stroke volume × 0.0144. Results: The stroke work (SW) was the most important factor associated with the LV mass (adjusted R2 = 0.422, p < 0.001), and body weight, age and gender were independent factors (adjusted R2 = 0.524). In a regression model, including stroke work, gender and height2.7, the LV mass was predicted by the equation: 79.4 + 6.35 × height (m2.7) + 0.45 × SW (g-m/beat)-15.6 × gender (male = 1, female = 2)(constant = 79.3 ± 14.7 g, adjusted R2 = 0.517, p = 0.001). Figure. No caption available. Conclusions: In this study using ambulatory BP, as with the previous studies, the stroke work, gender and height2.7 were important determinants of the left ventricular mass in Korean adults with a normal weight and normal blood pressure.